Structural state and redox behavior of framework Co(II) in CoIST-2: a novel cobalt-substituted aluminophosphate with AEN topology - Borges, C. (2013)
A highly crystalline cobalt-substituted aluminophosphate with an AEN topology, labeled CoIST-2, has been synthesized and characterized by powder XRD, TG/DSC, diffuse reflectance UV-vis spectroscopy, FTIR, EPR spectroscopy, and cyclic voltammetry. Both water and methylamine were shown to play a complementary role as dual template and space-filling agents during the hydrothermal synthesis of this material. The spectroscopic (EPR, UV-vis, and FTIR) and electrochemical characterization of the as-synthesized and calcined CoIST-2 material revealed the presence of two structurally different Co(II) species incorporated in its crystalline framework. The redox behavior and acidity was found to be different for these two Co(II) species. While one of these cobalt species corresponded to Bro¨nsted Co(OH)P acid sites, the other seemed to be associated with the presence of Lewis acid sites (Co0P type species). UV-vis spectra, typical of divalent cobalt in tetrahedral coordination, along with FTIR, demonstrated that only a fraction of the Co(II) ions undergo a reversible oxidative process after calcination in air and that some extraframework CoxOy type species are also generated through oxidation. The presence of divalent Co(II) in a slightly distorted tetrahedral coordination, both in the as-synthesized and calcined phase, was also detected with use of EPR data. The electrochemical oxidation of the two different framework Co(II) species and their further reduction could be evaluated semiquantitatively by cyclic voltammetry. The redox ability of CoIST-2 was also compared with that of two other cobaltsubstituted aluminophosphates involving different pore structures, namely CoAPO-40 and CoAPO-37, by using FTIR of adsorbed NO. It was found that the most readily oxidized ions were present in the more dense AEN topology, followed by the more open AFR and FAU structures, thereby emphasizing how the redox properties of transition metal ions in porous aluminophosphates are intimately linked to both the structure type/density of the host lattice and framework positions of the heteroelement.